PERANAN PROTEIN TENASCIN DAN PERUBAHAN KOMPOSISI LIPID PADA TRANSFORMASI KEGANASAN LESI PREMALIGNA LEUKOPLAKIA RONGGA MULUT (Pendekatan Biomolekuler) - Istiati Soehardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Leukoplakia is one of the premalignant lesion in the oral cavity that caused by many chemical materials, bacterial, virus, fungi and also to be supported by condition of the patient. The internal factors are genetic and promoter beside external factors as cigarette and alcohol can influence. Malignant tranformation depend on the type and location of leukoplakia. Recently reported that tenascin protein is the one of caused and lipid composition changes in mucous membrane will cause increasing of permeability and inhibition in the barrier function, that caused of the malignant changes. Furthermore malignant transformation can be examined by the biomolecular approach that can be contribute the most important information for the accurate changes.